2014
DOI: 10.1007/s10911-014-9329-5
|View full text |Cite
|
Sign up to set email alerts
|

The HER2 Signaling Network in Breast Cancer—Like a Spider in its Web

Abstract: The human epidermal growth factor receptor 2 (HER2) is a major player in the survival and proliferation of tumour cells and is overexpressed in up to 30 % of breast cancer cases. A considerable amount of work has been undertaken to unravel the activity and function of HER2 to try and develop effective therapies that impede its action in HER2 positive breast tumours. Research has focused on exploring the HER2 activated phosphoinositide-3-kinase (PI3K)/AKT and rat sarcoma/mitogen-activated protein kinase (RAS/MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 170 publications
0
51
0
1
Order By: Relevance
“…The phosphorylated tyrosines then act as docking sites for proteins which activate various signaling cascades including the RAS/RAF/MEK and PI3K/AKT pathways. 5 Although HER2 has no known ligand it maintains a continuously active conformation and can form heterodimers with other members of the EGF family, or homodimers when expressed at high concentrations. HER2 is the preferred binding partner of all the other ErbB receptors, 6,7 and also appears to amplify the signaling of the other receptors resulting in heterodimers with potent mitogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylated tyrosines then act as docking sites for proteins which activate various signaling cascades including the RAS/RAF/MEK and PI3K/AKT pathways. 5 Although HER2 has no known ligand it maintains a continuously active conformation and can form heterodimers with other members of the EGF family, or homodimers when expressed at high concentrations. HER2 is the preferred binding partner of all the other ErbB receptors, 6,7 and also appears to amplify the signaling of the other receptors resulting in heterodimers with potent mitogenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that further ampliication of the ErbB2 signaling may derive from its crosstalk with other signaling mediators. For instance, it has been demonstrated that ErbB2 can cross-talk with hormone receptors, insulin growth factor receptor (IGFR), protein phosphatases, transforming growth beta receptor (TGFR-beta) and ion channels resulting in a complex signaling network that contribute to tumor growth and progression [15].…”
Section: Molecular Mechanisms Of Erbb2 Activationmentioning
confidence: 99%
“…Several downstream signaling pathways are activated after ErbB2 receptor activation leading to the regulation of cell proliferation, growth and survival as well as invasion and angiogenesis [15]. Tyrosine residues phosphorylation resulting from receptor activation can recruit a variety of intracellular adaptor and scafold proteins that in turn mediate the activation of downstream signaling pathways.…”
Section: Canonical Erbb2 Signaling Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 15% and 23% of breast cancers show amplification and/or overexpression of the human epidermal growth factor receptor-2 (HER2) gene [3-5]. This receptor is mainly involved in signaling pathways that regulate cell proliferation, differentiation, migration, and apoptosis [6-9]. HER2 is a member of the epidermal growth factor receptor (EGFR) family of transmembrane tyrosine kinases.…”
Section: Introductionmentioning
confidence: 99%